Distribution of different hepatitis C virus genotypes in patients with hepatitis C virus infection - Salim, Farah Bokharaei (The WJG Press and Baishideng, 2010)
AIM: To investigate the presence of mixed infection and discrepancy between hepatitis C virus (HCV) genotypes in plasma, peripheral blood mononuclear cells (PBMCs), and liver biopsy specimens. METHODS: From September 2008 up to April 2009, 133 patients with chronic hepatitis C referred to Firouzgar Hospital for initiation of an antiviral therapy were recruited in the study. Five milliliters of peripheral blood was collected from each patient and liver biopsy was performed in those who gave consent or had indications. HCV genotyping was done using INNO-LiPA™ HCV II in serum, PBMCs, and liver biopsy specimens and then confirmed by sequencing of 5’-UTR fragments. RESULTS: The mean age of patients was 30.3 ± 17.1 years. Multiple transfusion was seen in 124 (93.2%) of patients. Multiple HCV genotypes were found in 3 (2.3%) of 133 plasma samples, 9 (6.8%) of 133 PBMC samples, and 8 (18.2%) of 44 liver biopsy specimens. It is notable that the different genotypes found in PBMCs were not the same as those found in plasma and liver biopsy specimens. CONCLUSION: Our study shows that a significant proportion of patients with chronic hepatitis C are affected by multiple HCV genotypes which may not be detectable only in serum of patients.